A glass fiber cloth reinforced anion exchange membrane and a preparation method thereof

By treating brominated polyphenylene ether with high-level bromination and quaternary phosphating and combining it with glass fiber cloth, the problems of low conductivity and insufficient mechanical properties of polyphenylene ether anion exchange membranes were solved, and high ion exchange rate and improved mechanical properties were achieved.

CN116487660BActive Publication Date: 2026-01-30CHENGDU LITHIUM ENERGY TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211424851.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-11-15
Filing Date
2022-11-14
Publication Date
2026-01-30
Estimated Expiration
2042-11-14

AI Technical Summary

Technical Problem

Existing polyphenylene ether anion exchange membranes suffer from low conductivity and insufficient mechanical properties.

Method used

By synthesizing highly brominated brominated polyphenylene ether and subjecting it to quaternary phosphating treatment, combined with glass fiber cloth reinforcement, the number of cationic groups and mechanical properties are improved.

Benefits of technology

It significantly improves the ion exchange rate and mechanical properties of the anion exchange membrane, and extends its service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

This invention relates to the field of fuel cell technology and discloses a glass fiber cloth-reinforced anion exchange membrane and its preparation method, comprising the following steps: S1, brominated polyphenylene ether is subjected to quaternization treatment to obtain a quaternization-modified brominated polyphenylene ether film-forming solution; S2, glass fiber cloth is immersed in the film-forming solution and cast to form an anion exchange membrane; in S1, the synthesis process of brominated polyphenylene ether is that alkylphenol is brominated and polymerized to obtain brominated polyphenylene ether. This invention synthesizes a brominated polyphenylene ether with a high degree of bromine substitution, and then subjectes it to quaternization treatment, resulting in a higher degree of quaternization and a greater number of cationic groups, thus achieving a higher ion exchange rate; at the same time, glass fiber cloth is used to improve the mechanical properties of the anion exchange membrane.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of fuel cell, in particular to a glass fiber cloth reinforced anion exchange membrane and a preparation method thereof. BACKGROUND

[0002] Fuel cell is a kind of high-efficiency, energy-saving energy conversion device, which generates electric current through the electrochemical oxidation of fuel and the electrochemical reduction of oxidant, avoiding environmental pollution. Among them, the polymer electrolyte membrane fuel cell is widely applied and researched due to its high power density, long service life and application field. According to the difference of membrane material in the cell, the polymer electrolyte membrane fuel cell is further divided into proton exchange membrane fuel cell (PEMFCs) and anion exchange membrane fuel cell (AEMFCs). Although PEMFCs has high conductivity, it is expensive and needs to use noble metal catalyst. Therefore, the current research gradually develops to AEMFCs.

[0003] The main component of AEMFCs is anion exchange membrane (AEMs), which plays a role in transferring hydroxyl ions and blocking fuel leakage. AEMs is a polymer membrane with selective permeability to anions, which is usually composed of a polymer backbone and a cationic group. AEMs is commonly used in water treatment, electrochemical industry and fuel cells. The structure of the polymer backbone determines the mechanical properties and thermal stability of the membrane, while the cationic group affects the conductivity and alkali resistance of the membrane. However, for anion exchange membranes, due to the working environment of high alkalinity (pH>14) and high temperature (>60℃), the stability is poor, and the degradation of the polymer main body and the alkaline group is easy to occur. At the same time, since the moving ion in AEMFCs is hydroxyl ion, and the diffusion coefficient of hydroxyl ion is lower than 1 / 4 of that of hydrogen ion, there are defects such as low hydroxyl conductivity and poor barrier property between two poles.

[0004] There have been extensive research reports on the preparation of alkaline anion exchange membranes at home and abroad. The existing polymer materials used for the preparation of alkaline anion exchange membranes include polyphenyl ether, polyether ketone, polyether sulfone, polyvinyl alcohol, etc. For polyphenyl ether anion exchange membrane, there have been some research reports, such as K Hari Gopi, who prepared polyphenyl ether with different degrees of chlorination by controlling the temperature and the amount of chlorinating agent during the reaction, and obtained a series of different quaternized polyphenyl ether anion exchange membranes. The results show that when the degree of chlorination is 40%, the QPPO membrane is applied to the cell device, and the maximum conductivity is 83 mS / cm measured at 70℃, but the effect of alkaline and high temperature stability still needs to be further improved.

[0005] As the patent with publication number CN108923056A discloses a preparation method of a novel polyphenyl ether anion exchange membrane with high conductivity, the patent first modifies polyphenyl ether by bromination and hydroxylation to obtain partially hydroxylated brominated polyphenyl ether, then reacts with epoxy chloropropane, and finally reacts with a quaternary ammonium reagent to obtain a high conductivity type polyphenyl ether anion exchange membrane. In the preparation process of the patent, bromomethylated polyphenyl ether is soaked in a sodium hydroxide solution to cause a hydroxylation reaction, and the reaction degree is low; although etherification and thermal crosslinking treatment are performed in the subsequent process to improve the mechanical properties of the membrane, the improvement of the ion conductivity of the membrane by quaternary ammonium treatment is limited. SUMMARY

[0006] <TECHNICAL PROBLEMS>

[0007] The current polyphenyl ether anion exchange membrane has the problems of low conductivity and insufficient mechanical properties.

[0008] <TECHNICAL SOLUTION>

[0009] In view of the above technical problems, the purpose of the present application is to provide a glass fiber cloth reinforced anion exchange membrane and a preparation method thereof. The present application synthesizes a brominated polyphenyl ether with a high degree of bromine substitution, and then performs quaternary phosphorus treatment, so that the degree of quaternary phosphorus treatment is higher and the number of cationic groups is more, thereby obtaining a higher ion exchange rate; at the same time, glass fiber cloth is used to improve the mechanical properties of the anion exchange membrane.

[0010] The specific content is as follows:

[0011] Firstly, the present application provides a preparation method of a glass fiber cloth reinforced anion exchange membrane, comprising the following steps:

[0012] S1 quaternary phosphorus treatment of brominated polyphenyl ether to obtain quaternary phosphorus modified brominated polyphenyl ether film forming solution;

[0013] S2 glass fiber cloth is immersed in the film forming solution to obtain an anion exchange membrane by flow casting;

[0014] In S1, the synthesis process of brominated polyphenyl ether is that alkyl phenol is brominated and polymerized to obtain brominated polyphenyl ether.

[0015] Secondly, the present application provides a glass fiber cloth reinforced anion exchange membrane obtained by the above preparation method.

[0016] <TECHNICAL MECHANISM>

[0017] The biggest problem faced by the anion exchange membrane is that the membrane has low conductivity under alkaline conditions, poor mechanical properties, and poor chemical stability, and is prone to degradation reaction in a strong alkaline environment, resulting in failure of the fuel cell. These defects greatly limit its application.

[0018] Thus, the application adopts a high degree of quaternary phosphorus polyphenyl ether as a matrix, uses glass fiber cloth as a reinforcing material, and performs bromination on raw material alkyl phenol, then polymerizes to obtain high bromination degree polyphenyl ether, and then performs quaternary phosphorus treatment on the obtained brominated polyphenyl ether, and glass fiber cloth is used as a reinforcing material, so that the mechanical properties of the anion exchange membrane are increased, and finally the membrane is formed by flow casting.

[0019] The application utilizes the characteristics that the para hydrogen atom of phenol is easy to undergo bromine substitution reaction, and makes the bromination reaction complete when the monomer is brominated, so that the degree of bromination is increased, thereby obtaining a high quaternary phosphorus matrix, which can effectively improve the ion conductivity, and the alkali resistance of the quaternary phosphorus group is higher than that of the quaternary ammonium group. Meanwhile, the glass fiber cloth is used as a reinforcing body, which can effectively improve the mechanical properties of the membrane and realize high functionalization.

[0020] <Advantages achieved by the application>

[0021] (1) The matrix material quaternary phosphorus polyphenyl ether synthesized by the application has the characteristics of simple synthesis process and high bromination degree, so that the content of cationic groups is high, and the ion conductivity of the anion exchange membrane can be obviously improved.

[0022] (2) The glass fiber cloth is used to composite with the matrix material in the application, the characteristics of different materials are combined, and the mechanical properties of the anion exchange membrane are enhanced, so that the service life of the anion exchange membrane is improved.

[0023] (3) The preparation process of the glass fiber cloth reinforced anion exchange membrane is simple and easy to operate, and is suitable for actual production. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical scheme and advantages of the embodiments of the application more clear, the technical scheme in the embodiments of the application will be clearly and completely described below. If the specific conditions are not specified in the embodiments, the conventional conditions or the conditions recommended by the manufacturer are used. If the reagents or instruments are not specified by the manufacturer, they are all conventional products that can be purchased in the market.

[0025] Firstly, the application provides a preparation method of a glass fiber cloth reinforced anion exchange membrane, which comprises the following steps:

[0026] S1: quaternary phosphorus treatment is performed on brominated polyphenyl ether to obtain quaternary phosphorus modified brominated polyphenyl ether film forming solution;

[0027] S2: the glass fiber cloth is immersed in the film forming solution, and the anion exchange membrane is obtained by flow casting;

[0028] In S1, the synthesis process of the brominated polyphenyl ether is as follows:

[0029] S11 alkyl phenol reacts with bromine water in the presence of a first catalyst to obtain 2,6-dimethyl-4-bromophenol;

[0030] S12 2,6-dimethyl-4-bromophenol is subjected to bromination reaction with N-bromosuccinimide in the presence of a free radical initiator to obtain brominated phenol;

[0031] S13 brominated phenol is subjected to oxidative coupling polymerization reaction in the presence of a second catalyst to obtain brominated polyphenyl ether.

[0032] In the present application, the bromination degree of the brominated polyphenyl ether is 50-80%.

[0033] In S1 of the present application, the synthesis process of the brominated polyphenyl ether is that alkyl phenol is first reacted with bromine water in the presence of an alkaline catalyst (a first catalyst), and then the product is reacted with N-bromosuccinimide (NBS) in the presence of a free radical initiator to obtain brominated phenol; the brominated phenol is subjected to oxidative coupling polymerization reaction in the presence of a second catalyst to obtain brominated polyphenyl ether.

[0034] In S11, the molar ratio of alkyl phenol to bromine water is 1:1-5, the first catalyst includes at least one of K2CO3, KOH, NaOH and Ca(OH)2, and the molar ratio of the first catalyst to bromine water is 1:1-10.

[0035] In S12, the molar ratio of 2,6-dimethyl-4-bromophenol to N-bromosuccinimide is 1:2-10, and the free radical initiator accounts for 3%-50% of the mass of N-bromosuccinimide.

[0036] The free radical initiator includes at least one of benzoyl peroxide (BPO), azobisisobutyronitrile (AIBN), azobisisoheptyl nitrile, dimethyl azobis isobutyrate and azobis isobutyl amidine hydrochloride (V-50).

[0037] In the present application, the alkyl phenol includes at least one of 2,6-dimethyl phenol, 2,6-diethyl phenol, 2,6-diisopropyl phenol, 2,3,6-trimethyl phenol, 2,6-di-n-propyl phenol, 2-methyl-6-tolyl phenol or 2,6-ditolyl phenol.

[0038] In S2 of the present application, the glass fiber cloth is subjected to quaternary ammonium modification treatment. The glass fiber cloth is grafted with cationic groups, which can increase the ion conduction sites and realize anion enrichment and migration. That is, before the glass fiber cloth is combined with the matrix material, the glass fiber cloth is subjected to modification treatment to graft long-chain cation exchange groups, so as to improve the electrical conductivity. At the same time, the grafted groups improve the thermal stability of the polymer, so that the comprehensive performance is improved.

[0039] In the present application, the process for modifying the glass fiber cloth by quaternization is that the silane coupling agent is added into alcohol to hydrolyze, to obtain A liquid; the double end group halogenated linear alkane is blended with (CH3)2N-R1-N(CH3)2 to obtain B liquid; R1 represents a linear alkyl with carbon atom number of 2-10; A liquid and B liquid are blended at a proportion of 1:1-3 in volume ratio, and the glass fiber cloth is soaked to obtain the glass fiber cloth modified by quaternization.

[0040] In the present application, the mass ratio of the double end group halogenated linear alkane and (CH3)2N-R1-N(CH3)2 is 1:1-3.

[0041] Specifically, the double end group halogenated linear alkane can be 1,2-dibromoethane, 1,3-dibromopropane, 1,4-dibromobutane, 1,5-dibromopentane, 1,6-dibromohexane, 1,7-dibromoheptane, 1,8-dibromo-octane, 1,9-dibromononane, 1,10-dibromodecane. The raw material I can also be that the halogen atom-Br in the above is replaced by F, Cl, I.

[0042] Specifically, the double end group halogenated linear alkane can be 1-iodo-2-bromo-ethane, 1-chloro-2-iodo-ethane, 1-bromo-3-iodo-propane, 1-chloro-3-iodo-propane, 1-bromo-4-iodo-butane, 1-chloro-4-iodo-butane, 1-bromo-5-iodo-pentane, 1-chloro-5-iodo-pentane, 1-bromo-6-iodo-hexane, 1-chloro-6-iodo-hexane, 1-bromo-7-iodo-heptane, 1-chloro-7-iodo-heptane, 1-bromo-8-iodo-octane, 1-chloro-8-iodo-octane, 1-bromo-9-iodo-nonane, 1-chloro-9-iodo-nonane, 1-bromo-10-iodo-decane, 1-chloro-10-iodo-decane.

[0043] Specifically, (CH3)2N-R1-N(CH3)2 can be N,N,N',N'-tetramethyl-1,2-ethanediamine, N,N,N',N'-tetramethyl-1,3-propanediamine, N,N,N',N'-tetramethyl-1,4-butanediamine, N,N,N',N'-tetramethyl-1,5-hexanediamine, N,N,N',N'-tetramethyl-1,6-heptanediamine, N,N,N',N'-tetramethyl-1,7-octanediamine, N,N,N',N'-tetramethyl-1,8-nonanediamine, N,N,N',N'-tetramethyl-1,9-decanediamine.

[0044] Further, R1 represents a linear alkyl with carbon atom number of 4-8.

[0045] In the present application, in S1, the molar ratio of -Br in brominated polyphenyl ether to quaternary phosphorus reagent is 1:1-6.

[0046] In the present application, the quaternary phosphorus reagent is tributyl phosphate and / or (4-bromobutyl)triphenylphosphonium bromide.

[0047] Secondly, the present application provides a glass fiber cloth reinforced anion exchange membrane obtained by the aforementioned preparation method.

[0048] <Embodiment>

[0049] Example 1

[0050] A preparation method of a glass fiber cloth reinforced anion exchange membrane, comprising the following steps:

[0051] (1) Synthesis of brominated polyphenyl ether

[0052] 2,6-dimethylphenol is dissolved in chloroform, heated, and bromine water is added dropwise while stirring at 60-100°C, the molar ratio of 2,6-dimethylphenol to bromine water is 1:1, then KOH is added, the molar ratio of KOH to bromine water is 1:1. After the dropwise addition is completed, wash with 5% sodium sulfite aqueous solution for 15 min until the solution is layered, add activated carbon to the oil phase and stir under reflux for 30 min, then immediately filter, filter the filtrate after cooling, wash the filter cake with anhydrous ethanol solution, and recrystallize to obtain the product, i.e. 2,6-dimethyl-4-bromophenol; then, 2,6-dimethyl-4-bromophenol is dissolved in acetonitrile, stirred and heated, at 80°C, first add NBS, then add BPO after complete dissolution, the molar ratio of 2,6-dimethyl-4-bromophenol to NBS is 1:2, and the mass fraction of BPO is 3% of NBS, react at this temperature for 15 h. Remove acetonitrile under reduced pressure, wash with anhydrous ethanol solution several times, and recrystallize to obtain the product, i.e. brominated phenol.

[0053] Take 20 g of brominated phenol and 100 mL of toluene in a beaker, and make it fully dissolved. At room temperature, take 0.6 g of CuCl, 48 mL of pyridine, and 200 mL of toluene in a four-necked flask, and introduce oxygen, and start stirring. Heat to 30°C, keep the temperature and stirring for 20 min, then slowly add the fully dissolved phenol-toluene solution in the beaker to the four-necked flask, keep the temperature and stirring during this process, react for 60-120 min, then add acetic acid to terminate the reaction. After the reaction is completed, add the acidified product dropwise into methanol, perform suction filtration, then wash with methanol and water several times, finally put the precipitate into a vacuum oven at 120°C, and dry for 6 h to constant weight, to obtain brominated polyphenyl ether.

[0054] (2) Grafting treatment of glass fiber cloth

[0055] A solution A was prepared by dissolving 4-(chloromethyl)phenyltrimethoxysilane 0.5 g in 10 ml of 95% ethanol aqueous solution, which was adjusted to pH 3-4 with oxalic acid and stirred;

[0056] A solution B was prepared by dissolving 1,6-dibromohexane 2 g and N,N,N,N-tetramethyl-1,6-hexanediamine 4 g in 10 ml of anhydrous ethanol and stirring;

[0057] The solution A and the solution B were mixed uniformly at a volume ratio of 1:1, and the glass fiber cloth was placed in the mixture for 30 min.

[0058] (3) Preparation of glass fiber cloth reinforced anion exchange membrane

[0059] The brominated polyphenyl ether was dissolved in DMAc to form a homogeneous solution with a concentration of 20%; a quaternary phosphorus reagent, tributyl phosphate (TBP), was added in a molar ratio of n(-Br):n(quaternary phosphorus reagent)=1:2, the reaction temperature was 80-120°C, and the stirring time was 1-3 h;

[0060] The treated glass fiber cloth was immersed in an appropriate amount of the above solution, and after the DMAc solution was volatilized, a quaternary phosphorus polyphenyl ether / glass fiber cloth composite membrane was formed, and the obtained composite membrane was dried in a vacuum oven.

[0061] Example 2

[0062] The difference between this example and Example 1 is that in (1), the molar ratio of 2,6-dimethylphenol to bromine water is 1:3, the molar ratio of 2,6-dimethyl-4-bromophenol to NBS is 1:4, the molar ratio of KOH to bromine water is 1:2, and the mass fraction of BPO to NBS is 5%.

[0063] Example 3

[0064] The difference between this example and Example 1 is that in (1), the molar ratio of 2,6-dimethylphenol to bromine water is 1:5, the molar ratio of 2,6-dimethyl-4-bromophenol to NBS is 1:5, the molar ratio of KOH to bromine water is 1:4, and the mass fraction of BPO to NBS is 10%.

[0065] Example 4

[0066] The difference between this example and Example 1 is that in (2), 1,6-dibromohexane 2 g and N,N,N,N-tetramethyl-1,6-hexanediamine 6 g were dissolved in 10 ml of anhydrous ethanol and stirred to obtain a solution B.

[0067] Example 5

[0068] The difference between this example and Example 1 is that in (3), n(-Br):n(quaternary phosphine reagent) = 1:5.

[0069] Example 6

[0070] The difference between this example and Example 1 is that 1,6-dibromohexane is replaced by 1,5-dibromopentane.

[0071] Example 7

[0072] The difference between this example and Example 1 is that 1,6-dibromohexane is replaced by 1-bromo-6-chloro-hexane.

[0073] Example 8

[0074] The difference between this example and Example 1 is that N,N,N,N-tetramethyl-1,6-hexanediamine is replaced by N,N,N',N'-tetramethyl-1,4-butanediamine.

[0075] <Comparative Example>

[0076] Comparative Example 1 Comparative Example 2

[0077] A new type of polyphenyl ether anion exchange membrane was prepared according to the preparation method in CN108923056A.

[0078] <Test Example>

[0079] Examples 1-5 and Comparative Example 1 were used as test samples, and examples were represented by E and comparative examples were represented by C. The following were measured:

[0080] (1) Ion exchange capacity

[0081] The ion exchange capacity (IEC) of the anion exchange membrane was determined by back titration.

[0082] First, about 100 mg of the AEM sample was immersed in 50 mL of a standard HCl solution (0.01 mol / L) for 48 h. Then, back titration was performed using a standard NaOH solution (0.01 mol / L) with phenolphthalein as an indicator. Finally, the sample membrane was dried at 80 °C to a constant weight.

[0083]

[0084] wherein M1 (mol / L) and V1 (mL) are the concentration and volume of the standard HCl solution, respectively, and M2 (mol / L) and V2 (mL) are the concentration and volume of the standard NaOH solution, respectively. Wdry (g) is the mass of the dry membrane.

[0085] (2) Water uptake

[0086] Anion exchange membrane (50 x 10 mm) was immersed in deionized water, soaked at a specified temperature for 24 h. After the membrane was taken out, the surface water was quickly absorbed with filter paper, then weighed and recorded as Wwet. Finally, the sample was vacuum dried at 80 °C to a constant weight, and its weight was measured and recorded as Wdry.

[0087]

[0088] (3) Conductivity

[0089] The hydroxide conductivity test of the cathode membrane is similar to the proton conductivity test method of the anode membrane, using a four-electrode probe method.

[0090] The test uses an electrochemical workstation in constant current mode (0.1 mA), with a scanning frequency range of 1 MHz-1000 Hz. The test process is as follows: place a 1 x 4 cm (oxygen oxygen type) anion exchange membrane in the clamp and connect it to the electrodes with 2 measuring voltages and 2 measuring currents, with a distance of 1 cm between the electrodes, place the clamp in deionized water, and immediately complete the test. The hydroxide conductivity is calculated as follows:

[0091]

[0092] Where R is the membrane resistance measured by the above method, L is the distance between the electrodes (1 cm), and W and d are the width (1 cm) and thickness of the membrane, respectively.

[0093] (4) Mechanical properties

[0094] Determined by the method of GB / T 1040.3-2006.

[0095] (5) Chemical stability

[0096] At 60 °C, the membrane was placed in a NaOH solution with concentrations of 1, 2, 3, 4, and 5 mol / L, respectively, and soaked for 24 hours, then washed repeatedly with deionized water, and the conductivity value of the membrane was measured to observe the change in conductivity of the membrane in different concentrations of NaOH solution.

[0097] The test results are shown in Tables 1-3.

[0098] Table 1 Conductivity performance of anion exchange membrane

[0099]

[0100] Table 2 Mechanical properties of anion exchange membrane

[0101]

[0102] Table 3 Alkali resistance of anion exchange membrane

[0103]

[0104] The function of the glass fiber cloth is mainly to improve the mechanical property of the anion exchange membrane. It can be seen from the scanning electron microscope analysis diagram of the brittle fracture section of the 200X and 3000X composite membranes that the glass fiber cloth has good combination with the polymer matrix material, and there is no obvious phase interface boundary. The anion exchange membrane can be used as a support material under external force or an alkaline environment.

[0105] The above only describes the preferred embodiments of the present application and is not used to limit the present application. For those skilled in the art, the present application can have various modifications and changes. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for producing a glass fiber cloth-reinforced anion exchange membrane, characterized by, The method comprises the following steps: S1: brominated polyphenyl ether is treated by quaternary phosphorus to obtain a quaternary phosphorus modified brominated polyphenyl ether film solution; S2: glass fiber cloth is immersed in the film solution and cast to obtain an anion exchange membrane; In S1, the synthesis process of the brominated polyphenyl ether is as follows: S11: alkyl phenol reacts with bromine water in the presence of a first catalyst to obtain 2,6-dimethyl-4-bromophenol; S12: 2,6-dimethyl-4-bromophenol is subjected to bromination reaction with N-bromosuccinimide in the presence of a free radical initiator to obtain brominated phenol; S13: the brominated phenol is subjected to oxidative coupling polymerization in the presence of a second catalyst to obtain brominated polyphenyl ether; In S2, the glass fiber cloth is subjected to quaternary ammonium modification treatment; The process for quaternary ammonium modification of the glass fiber cloth is as follows: The silane coupling agent is hydrolyzed by adding alcohol to obtain liquid A; Linear alkane with double end group halogen is blended with (CH3)2N-R1-N(CH3)2 to obtain liquid B; R1 represents linear alkyl with carbon atom number of 2-10; Liquid A and liquid B are blended at a volume ratio of 1:1-3, and the glass fiber cloth is soaked to obtain the quaternary ammonium modified glass fiber cloth.

2. The method according to claim 1, wherein in S11, the molar ratio of alkyl phenol to bromine water is 1:1-5, and the first catalyst comprises at least one of K2CO3, KOH, NaOH, and Ca(OH)2, and the molar ratio of the first catalyst to bromine water is 1:1-10.

3. The method according to claim 1, wherein in S12, the molar ratio of 2,6-dimethyl-4-bromophenol to N-bromosuccinimide is 1:2-10, and the free radical initiator accounts for 3%-50% of the mass of N-bromosuccinimide.

4. The method according to claim 3, wherein the free radical initiator comprises at least one of dibenzoyl peroxide, azobisisobutyronitrile, azobisisoheptyl nitrile, dimethyl azobis isobutyrate, and azobis isobutyl amidine hydrochloride. The alkyl phenol comprises at least one of 2,6-dimethyl phenol, 2,6-diethyl phenol, 2,6-diisopropyl phenol, 2,3,6-trimethyl phenol, 2,6-di-n-propyl phenol, 2-methyl-6-methylphenyl phenol, or 2,6-dimethylphenyl phenol. The mass ratio of the linear alkane with double end group halogen to (CH3)2N-R1-N(CH3)2 is 1:1-3. In S1, the molar ratio of -Br in the brominated polyphenyl ether to the quaternary phosphorus reagent is 1:1-6.

5. The method for preparing a glass fiber cloth reinforced anion exchange membrane according to claim 1, characterized in that, The anion exchange membrane reinforced by the glass fiber cloth is obtained by the method according to any one of claims 1-7.

6. The method of claim 1, wherein the glass fiber cloth reinforced anion exchange membrane is prepared by the steps of: (1) preparing a glass fiber cloth; (2) preparing a polymeric anion exchange membrane; and (3) laminating the glass fiber cloth and the polymeric anion exchange membrane. ​ 7. The method for preparing a glass fiber cloth reinforced anion exchange membrane according to any one of claims 1 to 6, characterized in that, ​ 8. A glass fiber cloth-reinforced anion exchange membrane, characterized by, ​

Citation Information

Patent Citations

  • Preparation method of novel polyphenyl ether anion-exchange membrane with high conductivity

    CN108923056A

  • Anion-exchange film, preparation method thereof and fuel cell

    CN103372381A

  • Polyphenyl ether type anion exchange membrane supported with tetra-amino quaternary phosphonium cation unit and preparation method of polyphenyl ether type anion exchange membrane

    CN110003462A